2015
DOI: 10.1097/bsd.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided Nucleoplasty With Radiofrequency Energy for the Treatment of Lumbar Disk Herniation

Abstract: The results of this study suggest that CT-guided nucleoplasty with radiofrequency energy is a relative effective and safe technique for treating leg pain caused by radicular encroachment. Furthermore, nucleoplasty combined with nerve root injection had achieved a significant greater improvement in pain management and functional level in short term (within 1 mo) after treatment than nucleoplasty alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, Ogbonnaya et al [ 22 ] reviewed 27 LDH patients treated with nucleoplasty and observed that 14 patients (51.9%) underwent reoperation of an open microdiscectomy due to a lack of significant improvement of clinical outcomes after nucleoplasty. Wu et al [ 23 ] showed that nucleoplasty combined with nerve root injection could significantly improve symptoms of pain and promote patients’ functional level compared with a single nucleoplasty treatment at the early stage after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ogbonnaya et al [ 22 ] reviewed 27 LDH patients treated with nucleoplasty and observed that 14 patients (51.9%) underwent reoperation of an open microdiscectomy due to a lack of significant improvement of clinical outcomes after nucleoplasty. Wu et al [ 23 ] showed that nucleoplasty combined with nerve root injection could significantly improve symptoms of pain and promote patients’ functional level compared with a single nucleoplasty treatment at the early stage after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Furthermore, RIN could relieve the symptoms of patients with lumbar disc herniation. 8 Kloth et al 9 reported that RIN could be preferred for treating radicular pain caused by disc herniation. Kumar et al 10 proved that RIN could relieve pain, treat functional disability and improve the quality of life of patients with discogenic low-back pain.…”
Section: Introductionmentioning
confidence: 99%